Condylar position and morphology in bilateral partially edentulous patients: a radiographic perspective - Asymal, Alhidayati; Nurrachman, Aga Satria; Astuti, Eha Renwi; Mulyani, Sri Wigati Mardi; Ramadhani, Nastiti Faradilla; Savitri, Yunita; Putri, Adinda Melanita Zulkarnain; Izza, Raden Lailatul (Ikatan Radiologi Kedokteran Gigi Indonesia, 2025)
Objectives: Tooth loss is a common oral health issue in the general population, with its prevalence increasing significantly with age. Tooth loss that is not immediately rehabilitated with dentures can lead to disruption of the occlusion pattern. This condition may be affected by the position of the condyle, but it can also lead to morphological alterations of the mandibular condyle. If this condition is left untreated for an extended period, these changes can significantly impact the temporomandibular joint (TMJ). Materials and Methods: The sample used in this study was secondary data from panoramic radiographs of bilateral partially edentulous patients who had high-quality radiograph standards. Results: The findings of this study demonstrate the alteration in mandibular condyle position, with 57.7% of cases showing anterior position and 13.7% showing retroposition in patients with bilateral partial edentulism. The most dominant condyle morphology distribution was found to be the pointed shape (36.3%), whereas the least was the flat shape (5.7%). Conclusion: In this study, the results showed that the anterior position and pointed shape were the most common position and morphology of the condyle. The distribution of this position was found to be higher in women than in men, with hormonal, anatomical, and habitual factors influencing the distribution of pressure on the TMJ.